THE EFFECT OF MEMRISE APPLICATION ON STUDENTS’ VOCABULARY MASTERY AT SEVENTH GRADE OF MTs PAB 1 HELVETIA - Nasution, Asnizar (BRIGHT VISION Journal of Language and Education, 2022)
The objective of this study was to determine whether or not the application of memrise had a significant effect on vocabulary mastery of seventh grade junior high school students. The aim of the research is to find out whether the use memrise application has a significant on the students’ ability in vocabulary. This research is a quantitative study with a quasi-experimental design. The implementation is carried out in class VII MTs PAB 1 Helvetia for the 2020/2021 school year. The population was 192 students and the researcher took 32 students for the experimental class and 32 students for the control class, which means 64 students as the sample. In data collection, researchers used a multiple choice test as an instrument. The tests performed were pre-test which was given before treatment and post-test which was given after treatment. Then, the data obtained were analyzed using the t-test with a significance level of 5% (0.05). Furthermore, the researcher found that the mean post-test score in the experimental class was higher than the control class (75.31> 66.40). The t test results also show that t0 (4.03) is higher than t table at a significance level of 5% (0.05) with 62 degrees of freedom of 2.039. Therefore, the results of 4.03> 2.039 result in H0 (null hypothesis) rejected and Ha (alternative hypothesis) accepted. Thus, the application of memrise has a significant effect on the vocabulary mastery of seventh grade in MTs PAB 1 Helvetia.